Digital Forensics in Open Journal Systems: Case Study on Security Breach and Data Recovery - Andi M. Yusuf; Dian Megah Sari; Musawwir (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
Open Journal Systems (OJS) has become the dominant platform for scholarly journal publication in Indonesia, with more than 8,500 active journals in 2024. However, the growing cyber threats targeting academic infrastructures demand the development of digital forensic methodologies specifically tailored to the OJS ecosystem. This research develops a comprehensive framework for digital forensic investigation on the OJS platform through the analysis of 45 security incidents that occurred in Indonesian scholarly journals during the 2022–2024 period. The proposed Digital Forensic for Academic Publishing (DFAP) methodology covers preservation, acquisition, examination, analysis, and presentation, specifically designed for the OJS architecture. The implementation of this framework in 12 real-world cases demonstrated a success rate of 89.3% in data recovery, 76.2% in perpetrator identification, and 94.4% in operational system restoration, with an average resolution time of 72 hours. The study also identified 15 common vulnerability patterns in Indonesian OJS installations and produced 28 security recommendations that can reduce incident risks by up to 67%. The main contributions of this research include the development of OJS-specific forensic tools, the standardization of investigation procedures for academic institutions, and the establishment of the Indonesian Academic Digital Forensic Database (IADFD) as a knowledge-sharing repository.